Infotainment: Kebebasan atau Kebablasan Ditinjau dari Kajian Ekonomi Politik Media - Endang Setiowati (Humaniora, 2010)
Infotainment as delivered on television occurs to be one controversial TV shows, often accused as a program that practically a "Social Duping". But, in reality these genres frequently achieve rating peak, which in certain will raise TV commercial due to profitable matters for Television Company. Article explores “conspiracies” that occurs based on variable interest between producers, broadcasting industry, rating institutions, and advertisements both for continuity and multiple profit. The main idea of how infotainment dominates both news and entertainment program is caused by social actors' demands that implement in press liberating process in Indonesia whose embrace of neo-liberalism which claimed that “the greater the play of the market forces, the greater the freedom of the press; the greater the freedom of the press, the greater the freedom of the audience choice”. It seems impossible to stop infotainment programs since that alone will subdue both corresponding institution and individual in a certain point of view. Therefore, a regulation that copes with this matter due to continuity of these genres is needed in overcoming matters of “Social Duping”.